Clamshell-Thorakotomie nach thorakalen Messerstichen - Rudolph, Marcus; Schneider, Niko; Popp, Erik (Der Unfallchirurg, 2017)
Resuscitation in the event of traumatic cardiac arrest was for a long time considered to be a less than promising technique to employ; however, current data indicate that the prospects of success need not be any poorer than for resuscitation due to cardiac distress. The targeted and rapid remedying of reversible causes can re-establish the circulatory function and the European Resuscitation Council (ERC) algorithm for traumatic cardiac arrest is a helpful guide in this respect. This case report illustrates the resolute implementation of this algorithm in the prehospital environment in the case of an attempted suicide by a thoracic knife wound.